PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA WARUNG SATE KLATAK PAK PONG BANTUL) - Adhitama, Muhammad Hendri; Sukardi, Sukardi (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to analyze the influences of prices, quality of products and services on purchasing decision in Pak Pong Klatak Satay Culinary in Bantul. The subjects of this research were customers of Pak Pong Klatak Satay Culinary in Bantul. The population of the study were people who purchased products of Pak Pong Klatak Satay Culinary in Bantul.  The samples were determined by accidental sampling method by total of 80 respondents. Data were collected by giving a list of questions / questionnaires to  respondents dealing with prices, products quality as well as services quality and how they influence the customers decision in purchasing the products. This study used a multiple linear regression analysis technique. The researcher tested the hypothesis using T test and F test. The test results  showed that prices have a positive but insignificant influence, products quality has a negative and insignificant influence. Meanwhile, services quality has a positive and significant influence. Prices, products and services quality contribute  to a simultaneously positive and significant influence upon customer’s purchasing decision as the significant value of 0,000 is smaller than 0,5. The prices variables, products quality and services quality are able to explain the purchasing decision variable in Pak Pong's klatak satay culinary at 35%  and  the  remaining 65% explained by other variables not included in the study.